Penggunaan Keigo dalam Konsep Uchi-Soto (Analisis Pada Drama Jepang Kaseifu No Mita Karya Kazuhiko Yukawa) - Fi Kharisma, Hadra; Rahayu, Nana; Aibonotika, Arza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT This study analyzes about the use of keigo in the concept of uchi-soto appearing on Japanese drama titled conversation Kaseifu No Mita by Kazuhiko Yukawa, which aims to identify and understand more about the situation and use keigo based on the concept of uchi-soto in daily conversation so that no more errors in use it in daily conversation, especially for Japanese learners at the University of Riau.The methodsthat are used in this research is descriptive and data analysis. In analyzing the data, the writer analyzes the use Keigo based uchi-soto situation of the conversation. This study shows that the results of the Japanese people differentiate the attitudes because of awareness of the acts, behave and conduct limitation that committed by a person towards his/her partner in a conversation by adjusting kinds of language / Japanese politeness level (keigo). Keywords:analysis, sosioliguistic, keigo, concepts, uchi-soto.